Menggugat Warisan Kolonialisme melalui Resistensi Post-Kolonialisme dalam Membangun Identitas Bangsa di Era Kontemporer - Frisca Dyan Areza; Suratih Muhamad Karo; Budi Mulyono (Integralistik, 2026)
This study aims to analyze how the legacy of colonialism has influenced the formation of Indonesia’s post-colonial national identity, as well as to examine the forms of cultural and social resistance that have emerged in the effort to build a more inclusive and independent national identity. The legacy of colonialism is not limited to physical structures, but also encompasses ideological, social, and cultural dimensions that continue to affect the lives of Indonesian people. This research employs a qualitative method with a literature review approach by examining various relevant sources, such as scholarly journals, books, indexed articles, and other supporting documents. The data were analyzed using content analysis, drawing on post-colonial theoretical perspectives, including the concepts of coloniality of power (Quijano), hybridity and mimicry (Bhabha), as well as the decolonization of knowledge. The findings indicate that resistance to colonial and global influences is manifested through the revitalization of local culture, the use of social media, and critiques of educational systems that continue to prioritize Western models. Although such resistance has developed significantly, major challenges remain, particularly in confronting globalization, which tends to drive cultural homogenization. This study contributes to a deeper understanding of how Indonesian society actualizes such resistance in the process of constructing a national identity that is more relevant to the global context and local cultural diversity. It also highlights the need for stronger and more inclusive policies that are responsive to the dynamics of local cultures across different regions of Indonesia.